Klasifikasi Perilaku Keuangan UMKM Medan dengan Machine Learning dan SHAP - Saliman; Rivaldi Lubis; Sunaryo Winardi; Mustika Ulina (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2026)
Good financial behavior is an important factor in sustaining micro, small, and medium enterprises (MSMEs), particularly in financial recording, debt management, and investment planning. Previous research using Structural Equation Modeling Partial Least Squares (SEM-PLS) identified financial attitude as the dominant factor influencing MSMEs’ financial behavior in Medan City. Based on these findings, this study develops a complementary machine learning-based approach to classify MSMEs’ financial behavior at the individual level and evaluate its consistency with SEM results through SHAP-based Explainable Artificial Intelligence (XAI). The dataset consists of 100 MSME respondents with seven main features, including three financial constructs and four demographic variables. Three ensemble algorithms, namely CatBoost, XGBoost, and Random Forest, were evaluated using hold-out and Stratified 5-Fold Cross-Validation. The results show that CatBoost achieved the best performance with 80.00% accuracy and 82.46% F1-score. SHAP analysis confirmed the dominance of attitude score and revealed the significant predictive contribution of demographic variables. Integrating machine learning and SHAP is an effective complementary approach to extend the understanding of MSMEs’ financial behavior comprehensively.